ACCELERATION OF DIGITAL SERVICE LITERACY OF BANK JATIM SYARIAH CAPEM PROBOLINGGO TO CUSTOMERS IN AN EFFORT TO MINIMIZE THE RISK OF DIGITAL TRANSFORMATION - Moh. Khoirul Anam; Saifuddin Saifuddin; Putri Nur Afrida (SEAN Institute, 2023)
This study aims to illustrate the importance of accelerating digital literacy to increase the literacy of Bank Jatim Syariah digital services to customers, so that customers are not easily exposed to digital-based fraud in online transactions, so as to minimize the risk of digital transformation. This research uses qualitative research with a descriptive approach based on the discovery of a social phenomenon or human problem that is currently occurring. The results of this study show that the acceleration of digital service literacy of Bank Jatim Syariah Capem Probolinggo applied to its customers is; First, providing literacy directly to customers when socializing Jconnect Mobile Bank Jatim Syariah. Second, conveying information in various media by following trends so that it is more attractive and easy to understand by customers and secures customer data information. Thus, it is an effective way to overcome the risk of digital transformation in the form of social engineering.